Agricultural cooperative — strategic way of industry development - Abdykaliyeva, Zh.Sh. (BUKETOV BUSINESS REVIEW, 2018)
The article deals with the role and importance of agricultural cooperation in ensuring the economic security of the country. The author of the study identifies the main problems hindering the development of agricultural cooperation: the preservation of the shadow economy, underdevelopment of commodity and logistics infrastructure, the presence of small agricultural producers. The role of the international practice of the organization of agricultural cooperatives in the production and sale of agricultural products is revealed by providing members of cooperation with material and technical resources and other services. The analysis concentrates on the main provisions of the adjusted laws on agricultural cooperation in the Republic of Kazakhstan. It also focuses upon the law of the Republic of Kazakhstan «on agricultural cooperatives». This article covers the work of the Ministry of agriculture of RK on attraction of small farms and subsidiary farms in cooperatives; formation of bases of creation of competitive agricultural commodity production; ensuring food security of the country; information and consulting support of agro-industrial complex. The current activities of cooperatives in the regions of the RK are analysed by revealing the main restraining factors of development of cooperative movement in the Republic. Some recommendations are presented for the unification of small farms in large agricultural cooperatives for the production, processing, storage, transportation and marketing of agricultural products.